The program “KASSI (KAki Sehat diabeteSI)” in the Elderly with Diabetes in the Target Area UPTD Sekar Jaya Health Center OKU - I Gusti Ayu Putu Desy Rohana; Gunardi Pome; Zanzibar Zanzibar; Lisdahayati Lisdahayati; D. Eka Harsanto; Saprianto Saprianto; Umar H.M (LPPM UIKA Bogor, 2023)
Diabetes is a Non-Communicable Disease (PTM) with the highest incidence rate in Indonesia. The low number of elderly (Elderly) visits to the Puskesmas since the Covid-19 Pandemic resulted in a low PTM performance in 2021, namely 89%. DM elderly in the working area of the Sekar Jaya Health Center UPTD with an incidence of leg injuries of 25%. The person in charge of the PTM program said that there were no assistance activities for monitoring the implementation of the Ankle Brachial Index in the elderly who had DM. Foot exercise is an exercise performed by people with Diabetes Mellitus (DM) to prevent injuries and help improve blood circulation in the extremities of the body (hands and feet). The solution to the partner problem implemented by the service team is the implementation of the KASSI (Healthy Diabetic Feet) program which aims to increase the Ankle Brachial Index in Elderly with Diabetes in the Sekar Jaya Health Center's UPTD Assisted Area. The activity was carried out for 2 months and was attended by 20 participants who regularly attended 5 meetings. The results of the implementation of the program were an increase in knowledge by 16.7% and skills by 59.9% in participants, as well as an increase in the average ankle-brachial index in 5 participants with an average value of 1.04 at the end of the activity.